Through My Lens: Photovoice-Based Videos as Depression Anti-Stigma among Generation Z Students - Rachmania, Firdhaniaty; Budiman, Rizva Rahmadien Salama; Budiman, Maharajni; Khairunnisa, Larasati; Gunanagara, Rival Muhammad Pangersa; Zakariyya, Farhan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
Depression is a mental issue closely related to the surrounding society, especially among Generation Z. The stigma associated with depression has led to several negative consequences, hindering life-long well-being. Developing an anti-stigma intervention regarding depression should be a collective concern. Therefore, this study aimed to investigate the effectiveness of photovoice-based videos as an anti-stigma intervention for depression. It included 29 Bandung-based Generation Z university students, using a pre experimental design with one group pretest-posttest method. In this study, data were analyzed using normality tests, categorizations, and paired sample t-tests. The t-test results showed that the screening of photovoice-based videos caused a significant difference between pretest and posttest scores, confirming the rejection of H0 and the acceptance of Ha. Therefore, photovoice-based videos proved effective in reducing depression stigma among Generation Z university students in Bandung.